2023
DOI: 10.3390/s23052405
|View full text |Cite
|
Sign up to set email alerts
|

Smart Cementitious Sensors with Nano-, Micro-, and Hybrid-Modified Reinforcement: Mechanical and Electrical Properties

Abstract: The current paper presents the results of an experimental study of carbon nano-, micro-, and hybrid-modified cementitious mortar to evaluate mechanical performance, energy absorption, electrical conductivity, and piezoresistive sensibility. Three amounts of single-walled carbon nanotubes (SWCNTs), namely 0.05 wt.%, 0.1 wt.%, 0.2 wt.%, and 0.3 wt.% of the cement mass, were used to prepare nano-modified cement-based specimens. In the microscale modification, 0.05 wt.%, 0.5 wt.%, 1.0 wt.% carbon fibers (CFs) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Thanks to the continuous deepening of research, fiber-reinforced concrete materials have come into being. A large number of tests demonstrate that fiber incorporation not only fully realizes the goal of improving the cracking resistance of concrete, but also has a positive effect on the concrete’s mechanical properties, electrical properties, and durability [ 9 , 10 , 11 ]. However, it is worth noting that different types of fiber admixtures have varying effects on the performance improvement of UHPC materials.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the continuous deepening of research, fiber-reinforced concrete materials have come into being. A large number of tests demonstrate that fiber incorporation not only fully realizes the goal of improving the cracking resistance of concrete, but also has a positive effect on the concrete’s mechanical properties, electrical properties, and durability [ 9 , 10 , 11 ]. However, it is worth noting that different types of fiber admixtures have varying effects on the performance improvement of UHPC materials.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on nanofibers, such as carbon nanofibers, have found that these fibers play an important role at the nanoscale level in the cement matrix. 20,21 Nanofibers have been used to improve the mechanical properties, mainly to enhance toughness and ductility, and to reduce cracking at the nanoscale level of cementitious materials. 22,23 The number of studies on using nanoparticles to enhance concrete properties is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials, which include many varieties in the form of very fine powder or liquid materials, as well as nanofibers, can be used. Many studies on nanofibers, such as carbon nanofibers, have found that these fibers play an important role at the nanoscale level in the cement matrix 20,21 . Nanofibers have been used to improve the mechanical properties, mainly to enhance toughness and ductility, and to reduce cracking at the nanoscale level of cementitious materials 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical capacities of cementitious composites, such as flexural strength, compressive strength, and toughness, or thermoelectrical properties such as conductivity, are powerfully affected by the additives' dispersion and the pore structure of the material [5,6]. In the pore characterization process, with micro-CT and pore size distribution, the diameter of pores plays a significant role [7] Although conventional volume-based theory considers the perfect spherical morphology according to the maximal ball algorithm, usually characterized by the pore size distribution of the material, these methods provide limitations in relating the anisotropic or heterogeneous pore properties.…”
Section: Introductionmentioning
confidence: 99%